A (in)efetividade do monitoramento eletrônico nas apenadas do regime aberto da penitenciária de reeducação feminina Maria Júlia Maranhão - Bandeira, Raquel Alves de Oliveira (2022)
The growing number of the prison population, associated with the absence of an adequate penal establishment during the progressive execution of the sentence, boosted the implementation of the electronic monitoring policy in Brazil. In this research, the object of study is the effects of electronic monitoring in the process of resocialization of convicts in the context of serving the sentence. Reports of convicts showed that such application has been configured as an obstacle to the aforementioned resocialization, which led, together with all the theoretical framework to which had access, to raise the following research question: what is the impact that electronic monitoring has conferred in serving the sentence with regard to social reintegration? It is noticed that only the granting of supervised freedom does not make the sentence effective. Based on this questioning, the general objective is to investigate the effects of electronic monitoring in the process of resocialization of inmates, more precisely, the repercussion of the electronic anklet in the job market, in the usual activities and in the social and family relationships. The study demonstrates its relevance as it addresses a crucial issue for a substantial segment of society, considering the potential availability of information and the current state of theorizing about it, which has little empirical appeal. In this sense, in order to achieve the proposed objective, the research is mainly characterized by the qualitativequantitative approach, as it involves both the understanding of the reasons related to the difficulties faced by convicts when using the electronic anklet and the apprehension of the percentage reality related to these difficulties, also using the technique of bibliographic data collection and field study, based on the analysis of reports collected through semi-structured interviews. For this research, there was a cut, so that the analyzes were restricted to the reports obtained from the inmates of the open regime of the Maria Júlia Maranhão Feminine Reeducation Penitentiary who made use of the electronic anklet, interviewed in 2021. Of the 50 participants, 49 were effectively interviewed, once the reports of the vast majority already pointed in the same direction. It is concluded that electronic monitoring does not make the execution of the sentence more effective, being a means of frustrating the convict’s relations with society, accentuating the social stigma, generating, in its turn, limitations and difficulties that permeate rights related to the dignity of the human person.